The postcard killers : a novel - Patterson, James, 1947-; Marklund, Liza, 1962- (New York : Little, Brown and Co., 2010)
A NYPD detective joins a Swedish reporter in a search for the killer of young couples in Europe, including his daughter and her boyfriend.
Keywords: Police -- Fiction; Americans -- Sweden -- Fiction; Women journalists -- Fiction; Couples -- Crimes against -- Fiction; Serial murderers -- Fiction; Stockholm (Sweden) -- Fiction; Mystery fiction